Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1532-5415.1993.tb06454.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Intramuscular Cefoperazone versus Intramuscular Ceftriaxone in Patients with Nursing Home‐Acquired Pneumonia

Abstract: Intramuscular cefoperazone and intramuscular ceftriaxone are safe and effective in the treatment of nursing home-acquired pneumonia. The clinical outcomes in both treatment groups support their use within this select population without the need for transferring the patient to an acute care hospital. Clinical studies are needed to evaluate the impact of such therapy on the control of health care expenditures within the nursing home facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 15 publications
0
21
0
2
Order By: Relevance
“…For example, mortality from pneumonia or lower respiratory tract infection varies widely in different samples of nursing home residents. In clinical trials excluding severely ill residents, mortality is typically !10% [65][66][67][68], whereas other studies based either in nursing homes or using hospitalized residents have reported between 10% and 40% mortality [11,12,14,[16][17][18]20,22,61,[69][70][71][72][73][74][75][76][77][78][79][80][81]. Different lengths of follow-up account for some of these mortality differences, but large differences in frailty undoubtedly also played a role.…”
Section: Discussionmentioning
confidence: 97%
“…For example, mortality from pneumonia or lower respiratory tract infection varies widely in different samples of nursing home residents. In clinical trials excluding severely ill residents, mortality is typically !10% [65][66][67][68], whereas other studies based either in nursing homes or using hospitalized residents have reported between 10% and 40% mortality [11,12,14,[16][17][18]20,22,61,[69][70][71][72][73][74][75][76][77][78][79][80][81]. Different lengths of follow-up account for some of these mortality differences, but large differences in frailty undoubtedly also played a role.…”
Section: Discussionmentioning
confidence: 97%
“…Pneumonia, along with other infections, was the leading cause of hospital admissions from nursing homes in a previous study at this institution 5 . Published treatment recommendations and studies in NHAP have generally been limited to issues of parenteral therapy for NHAP, either in the hospital or nursing facility 4,6–8 . Nursing home‐acquired pneumonia is also frequently treated in the NH with oral antibiotics and without extensive evaluation 9–11 .…”
mentioning
confidence: 99%
“…17 In a few small trials from the late 1980s or early 1990s, researchers found effectiveness of ceftriaxone or ciprofl oxacin to be equal when compared with similar antibiotics. [18][19][20][21] The ideal study design to test different regimens would be a randomized controlled trial; practical and ethical diffi culties make such a study unlikely. Consequently, we must rely on data from observational studies, attempting to control for differences between treatment groups.…”
Section: Introductionmentioning
confidence: 99%